Approach to the Study of Diathesis in Quechua: the Case of the Verbal Suffix -ku - Meneses Tutaya, Norma (2020)
In this article, I propose the existence of a grammatical diathesis subsystem of a derivative nature in Ayacucho Quechua. The derivative morphemes comprised within this subsystem are the reflexive -ku, the benefactive -pu, the assistive -ysi, the causative -chi and some combinations of suffixes such as -ykUpU, -naku and -naya, among others. The aim of this study is to prove that this diath esical subsystem works roughly like a functional concordance that involves actants expressed with diathesical derivative suffixes and those with inflectional suffixes of person. In order to show this derivative-inflectional diathesic interaction, the suffix -ku is analized.